Pengaruh Motivasi Kerja, Kompetensi Dan Kompensasi Terhadap Kinerja Karyawan Marketing Sales Pt Xyz - Suprastini dan Carunia Mulya Firdausy (Universitas Tarumanagara, 2019)
This research aims to find out the influence of work motivation, competency and compensation the performance of sales & marketing employees in PT. XYZ. Besides, it also has aim to analyze the influence of one variable to another variables. The data are collected through observation directly and also the distribution of questionnaires to the employees with the total 136 respondents. The analysis methods used in this research are descriptive and multiple linear regression. After the data analysis is done, it is found that all variables of work motivation, competency, and compensation have significant effect to the performance of sales & marketing employees in PT. XYZ with the ability to explain only 45%.